Impaired quality of life in systemic sclerosis and patient perception of the disease: A large international survey - Frantz, Camelia; Avouac, Jérôme; Distler, Oliver; Amrouche, Fazia; Godard, Dominique; Kennedy, Ann Tyrrell; Connolly, Kerry; Varga, John; Matucci-Cerinic, Marco; Allanore, Yannick (Seminars in arthritis and rheumatism, 2016)
The purpose of this study was to assess health-related quality of life (HRQoL) and disease perception in a large, international group of patients with systemic sclerosis (SSc). We placed a standardized questionnaire on a website for patient access. Socio-demographic information, disease characteristics, and self-assessment questionnaires—the Short Form 36 (SF-36) and the Revised Illness Perception Questionnaire (IPQ-R)—were collected. A total of 1902 patients from 60 countries were included. HRQoL appeared to be impaired in SSc, particularly for physical health (PCS, mean ± SD = 43.4 ± 23.4). SSc patients also had strong perceptions about the chronic nature and negative consequence of the disease, and experienced negative emotions due to SSc. Patients with diffuse cutaneous SSc had a poorer HRQoL than those with limited cutaneous SSc, for both physical (PCS, mean ± SD = 46.6 ± 23.7 vs. 39.8 ± 22.3; p < 0.0001) and mental components (MCS, mean ± SD = 53.8 ± 23.0 vs. 50.3 ± 23.2; p = 0.003). Late-stage SSc patients were more likely to perceive their disease chronic (p < 0.0001), less controllable (p = 0.03) and with more consequences (p = 0.008), but they had a better understanding of their disease and experienced fewer negative emotions. Raynaud’s phenomenon and gastrointestinal complications were the organ involvements with the greatest impact on QoL, they were the two variables associated with the most negative perception of illness severity. This study, performed on the largest group ever set up for this purpose, confirms the major impact on QoL and the negative perceptions of their disease expressed by SSc patients. However, the perception of this illness tended to improve with disease duration, suggesting that patients find effective coping strategies.